Bioconversion of Agro-Food Wastes into Biofuels and Biobased Chemicals - Longanesi, Luca <1986> (Alma Mater Studiorum - Università di Bologna, 2016)
In this work, different biorefineries strategies were used in order to produce different fuels and chemicals from agro – industrial by product, focusing in particularly on microbial fermentation processes. Mixed consortia and pure culture of Thermotoga neapolitana were used to produce biomethane (through anaerobic digestion) and biohydrogen, respectively from grape pomace and milk whey. Due to the lignocellulosic nature of this by products, white and red grape pomaces in the anaerobic digestion process were tested alone, or in co – digestion, in batch, fed – batch and continuous tests in a 29 L CSTR bioreactor. Furthermore, inhibition experiments were performed in order to better characterize the biochemical process and to evaluate the effect of, oxygen, acetic acid and lignocellulosic derived compounds to the biomethanization process. Besides that, the possibility to enrich this biorefinery to produce propanol from the mixture of VFAs originated in the first steps of AD was evaluated. Bio – H2 tests were performed with milk whey alone or in co – digestion with molasses both in a 116 ml microcosms – scale, both in a 19 L SPCSTR reactor, coupled to a membrane module separation system, to enrich the hydrogen purity. Milk whey was also investigated as only carbon source for the production of succinic acid, one of the Top 12 building block according to the U.S.A Department of Energy, using Actinobacillus succinogenes pure culture in a collaborative project between or department and the Flemish Institute For Technological Research. Besides batch and continuous fermentations, different aspects were studied, as an innovative procedure for a biofilm fermentation in 1 L PFR – type reactor, and the possibility to couple the fermenter to an innovative electrodialysis plant, used as ISPR (In Situ Product Recovery) technique without cell retention steps in between.